The fundamentals of C/C++ game development using target-based development on SBC's - Beuken, Brian (CRC Press, Taylor & Francis Group, 2018)
This book is aimed at giving novice coders an understanding of the methods and techniques used in professional games development. Designed to help develop and strengthen problem solving and basic C/C++ skills, it also will help to develop familiarity targeting and using fixed/restricted hardware, which are key skills in console development. It also demonstrates underlying principles of game coding in practical step by step ways to increase exposure and confidence in game coding concepts.